Gender Influence on School Climate and Organizational Silence Amongst Teachers in Anambra State - Okeke-James, Ndidiamaka J.; Igbokwe, Innocent C.; Anyanwu, Adeline N.; Obineme, Obiageli, P. (European Scientific Journal, ESJ, 2020)
This paper examines the gender influence on school climate and organizational silence among teachers in secondary schools in Anambra State, Nigeria. Correlational research design is used for the study. The population of the study consisted of all the 5498 teachers in 259 secondary schools in Anambra State, comprising 775 male and 4723 female teachers. Two structured questionnaires were adapted as the instruments for data collection. The internal consistency of the instruments was established using Cronbach alpha which yielded 0.81 and 0.91. Four research questions and four hypotheses guided the study. The study reveals that there is no significant relationship between the perception of teachers who teach in an open school climate and their organizational silence. Secondly, there is no significant relationship between the perception of male and female teachers who teach in a closed school climate and their organizational silence. Based on this, recommendations were made.